O crime organizado e as organizações criminosas: conceito, características, aspectos criminológicos e sugestões político-criminais - Ana Luiza Almeida Ferro (2006)
Study about organized crime and the criminal organizations, including a historical view and emphasizing the question of their concept, characteristics and criminological aspects, and suggestions in terms of criminal policy. Initially, it focuses the terminology, the origins and evolution of organized crime, the crime of “conspiracy” and its variations, the most relevant criminological theories and conceptions to the understanding of the phenomenon as a whole and in particular, principally Edwin Sutherland’s theory of differential association and his notion about white collar crime, the Mafia’s myth in the United States and in Brazil and the constitutional and structural models of organized crime and criminal organizations. In the nuclear part, it studies the theme of the concept and characterization of organized crime and the criminal organization, in a critical and propositional way, examining organized crime’s classification in the criminality universe, the comparison of the phenomenon with other criminal modalities and criminal law institutes, the concept and characterization of organized crime and the criminal organization in foreign and Brazilian doctrine and from the point of view of international organizations, the approach of the phenomenon in comparative criminal law, especially in American, German, French, Italian, Portuguese, Spanish, Argentinean, Chilean and Cuban law, as well as in Brazilian criminal law, through the analysis of article 288 of the Penal Code, of Act no. 9034, 05.03.95, of other statutes and of some bills, in construction of a concept of organized crime as much universal as possible, in which the connections of criminal organizations with public administration and its agents — particularly through corruption, in line with Winfried Hassemer —, and with the business world, for the nature of its operations, are essential distinctive elements. In the last part, it describes and classifies some of the main foreign and Brazilian criminal organizations and presents suggestions in terms of criminal policy and law modifications.